Brief Psychoeducational and Cognitive Therapy for Nightmare Disorder (BPCT-ND) - Álvarez-García, Horacio Balam; Jiménez-Correa, Ulises (Sleep Science, 2024)
In adults, nightmare disorder is related to sleep deprivation, drug consumption or abuse, or other comorbid sleep disorders such as insomnia or insufficient sleep syndrome. Behavioral treatment has solid scientific evidence in disorders such as insomnia and, more recently, parasomnias. The aim of the present study was to investigate the clinical effectiveness of a Brief Behavioral Telemedicine Therapy in Nightmare Disorder in a 23-year-old female patient. The procedure consisted of the case study, with pre and posttreatment measures as well as follow-up after 1 month; and the Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Paris Arousal Disorders Severity Scale, and a sleep diary were applied. In parallel with changes recorded in the sleep diary, a decrease in nightmares, sleepiness, and insomnia symptoms was observed when the intervention was finished. The behavioral intervention was clinically effective; therefore, the present case report provides information on behavioral treatments for nightmare disorder.
Keywords: sleepiness; sleep initiation and maintenance disorders; cognitive behavioral therapy; REM sleep parasomnias